Frequency of Preterm Birth After Cervical Cerclage - Parvez, Sumbal; Naeem, Rabia; Hina Gul; Nazma; Sidra Gohar; Sadia Bibi (Journal of Postgraduate Medical Institute, 2026)
Abstract Objective: The purpose of this research was to find out how often preterm births occur following cervical cerclage. Study Design: The study was a Descriptive study. Methodology: The research was done at Gynecology and Obstetrics Department, Lady Reading Hospital, Peshawar for a period of six months (from 21/12/2020 to 21/6/2021). A total of 101 individuals were chosen for the study, and their BMI using the formula Kg/m2 was recorded along with their age, weight on a weighing scale in a supine position, height on a height scale in a standing posture, parity, gestational age, obstetrical history, and history of current pregnancy. Cervical cerclage under general anesthesia following Macdonald’s techniques was performed and the participants were observed till their delivery to evaluate the determine the frequency of preterm births after cervical cerclage. Results: In the present study among 101 participants, the mean age was 30 ± 8.31 years. The selected 46% of the participants were primipara while 55% participants were multipara, in which 89% delivered at term, while 11% had preterm deliveries. Conclusion: The study concludes that frequency of preterm birth in participants having cervical competence, after cervical cerclage was 11%. Keywords: Preterm delivery, Cervical cerclage.